Unethical Admissions: Academic Integrity in Question - Ansah, Richard Hannis; Aikhuele, Daniel Osezua; Liu, Yao (Springer Netherlands, 2017)
The increasing unethical practices of graduates’ admissions have heightened concerns about the integrity of the academy. This article informs this important subject that affects the students, admission systems, and the entire scientific community, thus, representing an approach against scholarly black market activities including falsified documents and unethical practices by consultants and students’ recruitment agencies.